Human appropriation of net primary production related to livestock provisioning ecosystem services in Southern Patagonia - Peri, Pablo Luis; Rosas, Yamina Micaela; Martínez Pastur, Guillermo José (MDPI, 2022)
Human appropriation of net primary productivity (HANPP) integrates ecological and socioeconomic perspectives on land use by quantifying the amount of net primary production (NPP) appropriated by society through biomass harvest from the ecosystem. The main objective of this study was to determine the spatial patterns of HANPP related to lamb and wool production from sheep farms across the province of Santa Cruz. The HANPP was obtained by dividing the sum of the biomass used in livestock products (lamb and wool) by the NPP. In addition, we examined the spatial relationship between HANPP and potential plant biodiversity and net carbon balance at the farm level under livestock land use across our study region. At the regional level, livestock production accounted for an average of 11.35% of appropriated NPP, and HANPP ranged from 0.75 to 50%. The map of HANPP across Santa Cruz showed low values in the vegetation transition (ecotone) between Nothofagus antarctica forests and grasslands in the west, in the south, and in wetlands where the most productive rangelands dominate. High values were observed in the northwest and central areas of the province. There were differences in HANPP across vegetation types with mean values that varied from 3.93% in grasslands on the Humid Magellanic Steppe to 12.33% in the Central Plateau. Simple linear regression analysis for HANPP evaluated in Southern Patagonia showed a negative linear relationship (p < 0.05) with vascular plant biodiversity and net carbon balance at the farm level. The method used to map HANPP related to livestock provisioning ecosystem services (ES) in the present study (lamb and wool), may be integrated into decision support systems. In this context, low HANPP values (<9%) promote sustainability-oriented economies within the region. Furthermore, keeping plant biodiversity and net carbon balance at the farm level could bring Patagonian export commodities recognition in international markets.